Facile formation of Ag nanoworms based Janus nanofiber composites for efficient solar steam generation. (February 2023) - Wang, Shan-Jiang; Su, Dan; Zhou, Huan-Li; Yan, Xi; Zhang, Xiao-Yang; Zhang, Tong
Abstract: In this work, a flexible Janus composites membrane fabricated by large-scale electrospinning, a rapid plasma etching process, and reproducible surface modification is proposed for stable and efficient solar desalination. The upper hydrophobic plasmonic absorbers are used for effective solar absorption while the bottom hydrophilic polymer layer is for water supply and salt resistant. The heat stability and cycle tests demonstrate their superior performance for steam generation (energy conversion efficiency with 76.06% under 6 sun and stable water output with 7.533 kg m −2 h −1 ). Such Janus membrane provides an alternative way for direct solar desalination, which is achieved by a scalable and cost-effective process. Graphical abstract: (a) Structures of Janus membrane for solar desalination, with upper plasmonic Ag nanoworms based broad-band absorbers and bottom stable PAN layer for water supply and salt resistant. (b) The enlarged TEM image of proposed anisotropic plasmonic Ag nanoworms. (c) The corresponding evaporation rates of seawater under different illumination intensity with Janus membrane, Ag-PAN membrane and pure PAN. For Janus membrane, the energy conversion efficiency and water output under 6 sun were 76.06% and 7.533 kg·m −2 · h −1, respectively, which was ∼5 folds higher than Ag-PAN only. Image 1 Highlights: A nanoworms-like perfect plasmonic absorbers were prepared by a simple synthesis strategy. 'hot spots' effects and light-trapping effects both contribute the superior light harvesting and light-to-heat conversion. The proposed Janus structure alleviates the damage to membrane from salt and facilitates steam generation. The membrane demonstrates the abilities of portability, reproducibility as well as fabrication with large-scale. The unique membrane shows excellent thermal stability and steam generation performance.